2019
DOI: 10.1212/cpj.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Practice Current

Abstract: A common complaint after concussion is the development of new or worsening headaches which can make it difficult or even impossible for patients to work or function in their day-to-day lives. Uncertainties associated with the complaints and a wide variety of approaches exist regarding the appropriate work-up and management of these patients. Areas of ongoing debate include the need for neuroimaging; optimal, acute, and preventative treatment; and proper counseling and expectation management. Given the wide var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…There are no available guidelines for treating posttraumatic headache, and there is extraordinary variability in treatment practices as a result. A global survey of physicians treating PTH found that the three most utilized interventions included reassurance, education about lifestyle factors affecting headache, and prescription of headache preventative medication [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are no available guidelines for treating posttraumatic headache, and there is extraordinary variability in treatment practices as a result. A global survey of physicians treating PTH found that the three most utilized interventions included reassurance, education about lifestyle factors affecting headache, and prescription of headache preventative medication [5].…”
Section: Introductionmentioning
confidence: 99%